Molecular Surgical Pathology - Cheng, Liang.; Cheng, Liang.; Eble, John N.; Eble, John N. (Springer New York : Imprint: Springer, 2013)
Molecular Surgical Pathology provides a concise review of recent advancement of molecular pathology in each organ system. The text is intended as a “first knowledge base” in the rapidly evolving field of molecular pathology and is organized in a user friendly outline format. Each chapter is organ-based and covers important aspects of molecular pathology and its impact on our daily practice of surgical pathology. The topics presented herein constitute the fundamentals and core base of knowledge required for the daily practice of surgical pathology. This book focuses on the practical utilities of molecular techniques and molecular biomarkers in daily practice of surgical pathology. The emphasis is on the impact of molecular pathology for tumor classification, diagnosis and differential diagnosis as well as its implications for patient management and personalized care. Numerous tables, diagrams and color illustrations are included throughout.  Molecular Surgical Pathology will prove a very useful resource for pathologists in training who are preparing for the Board and in-service examination.  It will also be a unique and invaluable resource for medical oncologists, physicians, other medical professionals and basic research scientists with interest in molecular pathology of human cancers.